PENERAPAN STRATEGI PEMASARAN DALAM PERSAINGAN BISNIS PASAR DI PT. ASH SHOFWAH GROUP TOUR HAJI DAN TRAVEL: PENERAPAN STRATEGI PEMASARAN DALAM PERSAINGAN BISNIS PASAR DI PT. ASH SHOFWAH GROUP TOUR HAJI DAN TRAVEL - Moh. Hafid, Moh. Hafid; Asmito, Asmito; Hasan, Khofifurrahman (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
Ash Shofwah Group Tour Hajj and Travel which has an address in the village of Curah Kalak, Jangkar District, Situbondo Regency is required to increase the number of prospective pilgrims and Umrah pilgrims every year. through the treatise above, it is necessary to apply the right marketing strategy considering that in Situbondo Regency there are many agents offering Hajj and travel tour services of the same type as competitors in Market Business competition. to carry out strategic roles and functions is to socialize PT. Ash Shofwah Group Tour Hajj and Travel to prospective pilgrims who have an interest in going to Mecca and Medina. The response in the Situbondo community shows that PT. Ash Shofwah Group Tour Hajj and Travel has not implemented a marketing strategy to the fullest, so that many people still do not properly understand the services offered by Ash Shofwah.